Identification of proteins that interact with DWNN domain of SNAMA a member of a novel protein superfamily - Rakgotho, Patrick Mpho (My University, 2008)
SNAMA is a 142 kDa Drosophila melanogaster protein, which consists of the uncharacterized conserved domain with no name (DWNN), zinc and RING finger-like motifs. The primary structure of SNAMA suggests that it might play an important role in cell cycle regulation and apoptosis. Previous studies revealed that homozygous SNAMA mutants underwent ectopic apoptosis which resulted in recessive lethality. SNAMA orthologues such P2P-R, PACT and RBBP6 are involved in cell cycle regulation, whereas Mpe1 is involved in mRNA processing. The aim of this study was to map out the role of SNAMA by isolating proteins which interact with it. DWNN was inserted into pGEX6P-2, phylexzeo plasmid (bait) and the Drosophila 0-12 hours cDNA library inserted in pJG4-5 (prey). The bait and the prey plasmid were used to transform appropriate yeast cells to probe for interacting proteins in yeast two hybrid assays, whereas the pGEX6P-2 was used for heterologous overexpression of DWNN in E. coli. Immunoprecipitation assays were also carried out with the crude protein extract from embryos, adult wild type, SNAMA mutant flies and the overexpressed protein using antibodies against SNAMA, Drosophila p53 Human DWNN and GST. The hybrid assay did not produce any interactors. Some of the proteins obtained from the immunoprecipitations were isolated and sequenced. The proteins identified were hsp82, Hsp70 and CG2985-PA. Data obtained from the immunoprecipitations suggest that SNAMA like Dmp53 might be involved in cell cycle regulation.
Keywords: DWNN; Dmp53; SNAMA; APOPTOSIS